2011
DOI: 10.1590/s0006-87052011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Enxertia em figueira 'Roxo de Valinhos' por borbulhia e garfagem

Abstract: ResumoCom o intuito de desenvolver um protocolo de enxertia em estacas não enraizadas de figueira 'Roxo de Valinhos' (Ficus carica L.), foram realizados dois experimentos com aplicação de duas técnicas de propagação: borbulhia e garfagem. No primeiro experimento, estacas lenhosas de 20 cm de comprimento, coletadas da porção mediana dos ramos, de junho a setembro, foram enxertadas por borbulhia tipo placa e "T" normal. No segundo experimento, os propágulos foram coletados em julho e as estacas foram enxertadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other studies also observed reduced graft survival when working with patch grafts (KOTZ et al, 2011;WENDLING et al, 2016), which caused poor cicatrization of the bud, and led to graft death. However, further studies are needed to clarify these results.…”
Section: Resultsmentioning
confidence: 98%
“…Other studies also observed reduced graft survival when working with patch grafts (KOTZ et al, 2011;WENDLING et al, 2016), which caused poor cicatrization of the bud, and led to graft death. However, further studies are needed to clarify these results.…”
Section: Resultsmentioning
confidence: 98%
“…For Kotz et al (2011), the introduction of varieties or species of the genus Ficus tolerant to nematodes is essential, as well as to test the potential propagation of the other resistant species found in Brazil, and new canopy varieties, for the diversification of the Brazilian ficiculture.…”
Section: Production Of Seedling By Propagation -mentioning
confidence: 99%
“…Averages followed by the same uppercase letter in the line and the same lowercase letter in the column, do not differ from each other by the Tukey test at 5% probability. Source:Kotz et al (2011) Grafting by cleft graft method in 'Roxo de Valinhos' fig tree,Kotz et al (2011) obtained adequate results in relation to the percentage of live grafts (81.7%), demonstrating satisfactory development of seedlings and good morphophysiological compatibility.…”
mentioning
confidence: 99%
“…Fig breeding studies for the development of new fig tree selections are costly since the pomological characteristics of the flowers are located within a closed receptacle (syconium) that has a small opening, making pollination difficult. Thus, the genetic diversity of most F. carica species is based on spontaneous mutations that are only multiplied through cuttings (Kotz, Campagnolo, Chagas, & Dalastra, 2011).…”
Section: Introductionmentioning
confidence: 99%